Recent trends in parenthood in Swedish same- and different-sex legal unions: emerging gender and socioeconomic differences - Stefanie Mollborn; Martin Kolk; Marie Evertsson (Genus)
Abstract Parentalization, or becoming a parent and being legally and socially recognized as such, has long been constrained for sexual minorities. Although many studies have examined the outcomes of children of same-sex couples, relatively less attention has been paid to researching parents in same-sex unions themselves. In Sweden, changing policy and social contexts have successively eased many disparities in access to parenthood for sexual minorities. Analyzing 27 years of Swedish administrative register data starting from the legal recognition of same-sex unions in 1995, we examined time trends in the prevalence of parenthood (coresidence with children under 18) and the sociodemographic characteristics of people with versus without coresident children in same- versus different-sex legal unions. We expected to document considerable changes over time as policy contexts, parentalization disparities, and minority stressors evolved. Results show that parenting increased over time within same-sex legal unions, with women becoming much more likely to parent while parenting remained rare in male-male legal unions. Mothers in same-sex legal unions became more similar over time to mothers in different-sex marriages, whereas fathers in same-sex legal unions were a highly selected group relative to fathers in different-sex marriages, mothers in same- and different-sex legal unions, and people without coresident children in same-sex legal unions. Sex, parenthood, and especially their interaction are important for understanding the characteristics and family formation experiences of people in same-sex legal unions.